Analysis of an Applied Core Collection of Adzuki Bean Germplasm by Using SSR Markers - Li-xia WANG; Xu-zhen CHENG; Su-hua WANG; Jing TIAN (Journal of Integrative Agriculture, 2012)
Genetic diversity of 158 accessions of an applied core collection of adzuki bean (Vigna angularis) and 18 wild genotypes were assessed by using 85 microsatellite markers. With an average of 5.81 alleles per locus, 493 alleles were detected, and their distribution frequencies lower than 5% accounted for 73.02% of the total number. The distributions of alleles between the cultivated and the wild adzuki bean germplasm are different, with a higher allelic diversity in the wild germplasm than that of the cultivated ones. An obvious genetic differentiation was also observed between the wild and the cultivated adzuki beans, and SSR markers may be useful in study identification and classification of them. Among cultivated adzuki bean, the genetic similarity coefficient varied from 0.366 to 0.939. Genetic structure analysis can clearly separate the wild genotypes from the cultivated adzuki bean, and also can divide the cultivated ones into different populations, as these populations are closely agreeable with the ecological regions where they originally grow. The results of this study will be useful in arranging local breeding programs, especially in the aspect of parental combinations or identification of progenies. These SSR markers can also provide important information to explain the genetic relationship between the cultivated and wild adzuki beans, and to accelerate the wild gene resources in broadening the gene pool in breeding program.